Recreating the Horizontal Magnetic Field at Colaba During the Carrington Event With Geospace Simulations - Seán P. Blake; Antti Pulkkinen; Peter W. Schuck; Alex Glocer; Denny M. Oliveira; Daniel T. Welling; Robert S. Weigel; Gary Quaresima (Space Weather)
Abstract An intriguing aspect of the famous September 2, 1859 geomagnetic disturbance (or “Carrington” event) is the horizontal magnetic (BH) data set measured in Colaba, India (magnetic latitude approximately 20°N). The field exhibits a sharp decrease of over 1,600 nT and a quick recovery of about 1,300 nT, all within a few hours during the daytime. The mechanism behind this has previously been attributed to magnetospheric processes, ionospheric processes or a combination of both. In this study, we outline our efforts to replicate this low‐latitude magnetic field using the Space Weather Modeling Framework. By simulating an extremely high pressure solar wind scenario, we can emulate the low‐latitude surface magnetic signal at Colaba. In our simulation, magnetospheric currents adjacent to the near‐Earth magnetopause and strong Region 1 field‐aligned currents are the main contributors to the large Colaba BH. The rapid recovery of BH in our simulated scenario is due to the retreat of these magnetospheric currents as the magnetosphere expands, as opposed to ring current dynamics. In addition, we find that the scenario that best emulated the surface magnetic field observations during the Carrington event had a minimum calculated Dst value between −431 and −1,191 nT, indicating that Dst may not be a suitable estimate of storm intensity for this kind of event.